RESPON MASYARAKAT TERHADAP REKLAMASI LAHAN BEKAS TAMBANG SEMEN SEBAGAI EKOWISATA DI DAERAH SALE KABUPATEN REMBANG - Sudarti; Siti Hindun Hindiyati (UHN IGB Sugriwa Denpasar, 2021)
Mining is one of the activities that has a bad impact on the environment and has a positive impact on the surrounding community. With mining, the community can make a living by working as part of the company, and on the other hand mining also has a negative impact which can remove the balance of the ecosystem through massive land dredging. The theory used is the response theory, which is the response, reaction and answer. The responses taken were from the surrounding community in the Sale area, Rembang Regency, and the response from the company. There are several company responses that are inversely proportional to the response of the community regarding the existence of reclamation. The hope of the community is that with mining, in the end when it is not used, land returns or reclamation must be carried out. The research method used is descriptive quantitative with respond using 60 people Sale regency, in which the entire population is used as research respondents. Techniques and data collection used were observation and interviews. The results showed that the whole community was willing if the ex-mining land that was not used would be handed over to the community and micro-scale reclamation was carried out as ecotourism. With a note, at least the company must provide a small amount of operational costs and compensation for community land.